THE ISLAMIC ETHICS AND INTEGRITY IN CONCEPTUALISING ISLAMIC ACCOUNTING CONCEPTS - Norazita Marina Abdul Aziz; Fadzila Azni Ahmad (Journal of Islamic, Social, Economics and Development, 2019)
Islamic ethics can be regarded as a part of Islamic axiological stances in scrutinisingthe integrity and transparency issues. In line with this, the axiological stances in constructingIslamic accounting concepts involves the delineation of the moral values and ethics in securingthe integrity through Islamic monitoring (hisbah). In fact, the philosophical position derives fromthe true knowledge founded in the Al-Quran, Hadis, Ijmak and Qiyas in bringing justice to life andthe hereafter. The articulation of Islamic accounting concepts from the Islamic philosophicalstances highlight the moral and ethical functions in constructing the concepts. The adherence toShari’ah Islami’iah is a form of worship, the role of Islamic Perspective of Accounting (IPA) isthus an act of worship in fulfilling obligations to Allah (God), society and self in achieving AlFalah (rewards in this world and hereafter). The paper inductively employed qualitative as aresearch method in contextualising the Islamic accounting concepts within its values andprinciples, which can be translated within the Islamic social accountability engagement and moralimperatives. Thus, the study is conducted to provide a holistic view of the underlying ethical valuesand morality principles of the Shari’ah Islami’iah (Islamic teachings) to establish integrity andtransparency. In line with this, the Islamic moral values and ethical conduct of an individual isessential in delineating the relationship of between man and Allah; man and another man; andlastly, man and nature (through the conception of hablum minnallah, hablum minnas). Theontological position is founded from the Tawhidic position, which underpins the concept ofOneness of the God. Parallel to this, the epistemological foundation follows the understanding ofthe scope of social integrity and Islamic monitoring (hisbah) as an underpinnings knowledge thatmay construct the evidence of tolerance, moral and ethical values within Islamic setting.